2001
DOI: 10.1073/pnas.251367498
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in transmembrane helix–helix interactions can define a hierarchy of stability for sequence variants

Abstract: The folding, stability, and oligomerization of helical membrane proteins depend in part on a precise set of packing interactions between transmembrane helices. To understand the energetic principles of these helix-helix interactions, we have used alaninescanning mutagenesis and sedimentation equilibrium analytical ultracentrifugation to quantitatively examine the sequence dependence of the glycophorin A transmembrane helix dimerization. In all cases, we found that mutations to alanine at interface positions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
204
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 29 publications
(38 reference statements)
7
204
0
Order By: Relevance
“…The solution NMR structure of GpA further confirmed how the presence of the two Gly residues in the interface can facilitate the close approach of helices, thereby allowing extensive backbone-backbone and side chain-side chain interactions to occur (12). Analytical ultracentrifugation experiments have shown that mutation of any interfacial position along the GpA-TM to Ala is energetically costly (42). This is most significantly pronounced with Gly 79 and Gly 83 , where the dimer is destabilized by 1.7 and 3.2 Kcal/mol, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…The solution NMR structure of GpA further confirmed how the presence of the two Gly residues in the interface can facilitate the close approach of helices, thereby allowing extensive backbone-backbone and side chain-side chain interactions to occur (12). Analytical ultracentrifugation experiments have shown that mutation of any interfacial position along the GpA-TM to Ala is energetically costly (42). This is most significantly pronounced with Gly 79 and Gly 83 , where the dimer is destabilized by 1.7 and 3.2 Kcal/mol, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, with the exception of Arg 110 , each of these charged residues is conserved among CTPs of widely divergent origin (11). Second, the amino-terminal segment of TMDIII contains the dimerization consensus sequence 115 GXXXG 119 , which is thought to be involved in formation of a high affinity association between transmembrane domains (15)(16)(17)(18)(19) and is conserved among CTPs (11). Importantly, we have demonstrated by two different approaches that the CTP exists as a homodimer in solution (13).…”
mentioning
confidence: 83%
“…[8][9][10][11][12] Although most hydrogen-bonded sidechain interactions that have been experimentally measured in membrane proteins appear to make relatively modest contributions, [21][22][23][24][25][26][27] some have been measured as high as 1.8 kcal/mol and in theory it is possible that they could be made even stronger. 26,28 Thus, it seems reasonable to expect that the number of transmembrane interhelical hydrogen bonds might increase in thermophiles.…”
Section: Interhelical Hydrogen Bonding In Thermophiles and Mesophilesmentioning
confidence: 99%